South Africa Diagnostic Review of Consumer Protection in Non-Credit Financial Services : Volume 2. Review against Good Practices - World Bank (World Bank, Washington, DC, 2017)
The consumer financial services sector in South Africa is among the most sophisticated in the world, yet nearly 40 percent of the population, especially blacks, use no formal financial services. The now ubiquitous mobile phones are dramatically changing the landscape of digital financial services but weak financial literacy and general literacy of the underserved population remain the Achilles Heel. At the same time, weak competition in the South African financial services sector is an issue – just 4 banks control over 80 percent of retail banking and over 90 percent of personal transactions, maintaining rates and fees above competitive levels. The 2010 FinScope survey found that consumer trust was higher in informal financial institutions than in the formal ones such as banks. The South African Government has embarked on a substantive program of improving the financial sector legislation and establishing a full market conduct regulator. Presented in two volumes, this World Bank’s review compares the South African framework for financial consumer protection (FCP) to international practice and provides recommendations to strengthen it. Volume I summarizes South Africa’s FCP policies, describes the recent surveys, and sets out the key findings and recommendations of the Review. Volume II provides an assessment of banking, securities, insurance, and private pensions segments and discusses the key issues in retail payments and remittances and financial education.